MODEL PEMBELAJARAN BAMBOO DANCING UNTUK MENINGKATKAN AKTIVITAS BELAJAR SISWA KELAS III SD NEGERI 015 RAMBAH SAMO - Eni Marta; Rinja Efendi; Elvina Elvina; Hasrijal Hasrijal; Rejeki Rejeki; Risna Mutiara Arni (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
Based on observations made by researchers at SD Negeri 015 Rambah Samo, problems were found in class III science learning. The learning strategy used by the teacher is monotonous. Learning is not running effectively, many students chat and do not pay attention to the teacher's explanation. So that student learning activities become less optimal and student learning outcomes are low. Based on the problems found, the researchers applied the bamboo dancing learning model to science learning. With the aim to improve student learning activities. This type of research is Classroom Action Research (CAR). The subjects in this study were 25 grade III students, consisting of 8 male students and 17 female students. The research was carried out for 2 cycles, each cycle consisting of 2 meetings. Data collection techniques using observation of teacher activities and student activities, documentation. The results showed that after applying the bamboo dancing learning model to science learning, the learning activities of class III students at SD Negeri 015 Rambah Samo increased. Research shows that the percentage of teacher activity in cycle I was 72.5% and cycle II increased to 90% which was categorized as very good. Student learning activity in cycle I was 71.25% and in cycle II increased to 87%. So from cycle I to cycle II student learning activities increased by 15.72%.